2018
DOI: 10.1007/s00464-018-6368-9
|View full text |Cite
|
Sign up to set email alerts
|

An ERAS protocol for bariatric surgery: is it safe to discharge on post-operative day 1?

Abstract: A cost-effective ERAS protocol for laparoscopic sleeve gastrectomy results in shorter length of stay, without increase in peri-operative morbidity or readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
1
25
0
1
Order By: Relevance
“…28 In terms of postoperative morbidity, a systematic review and meta-analysis described no or low influence on morbidity. 17 In accordance with these results, Lam et al 29 supported a shorter LOS in patients undergoing SG, without increasing 30-day perioperative morbidity (3.6%, P = .4) or readmission rates (1.2%, P = .8). Our findings are congruent with the previous reported studies, showing a decreasing trend regarding readmissions and postoperative adverse events.…”
Section: Outcomes Of the Implementation Of Eras Protocolsmentioning
confidence: 62%
“…28 In terms of postoperative morbidity, a systematic review and meta-analysis described no or low influence on morbidity. 17 In accordance with these results, Lam et al 29 supported a shorter LOS in patients undergoing SG, without increasing 30-day perioperative morbidity (3.6%, P = .4) or readmission rates (1.2%, P = .8). Our findings are congruent with the previous reported studies, showing a decreasing trend regarding readmissions and postoperative adverse events.…”
Section: Outcomes Of the Implementation Of Eras Protocolsmentioning
confidence: 62%
“…With improved understanding of optimal patient recovery after surgery and the advent of enhanced recovery after surgery (ERAS), many patients are now going home within 2 to 3 days following bariatric surgery [ 35 , 36 ]. A meta-analysis looking at the length of stay following bariatric surgery in ERAS and non-ERAS cohorts demonstrated a mean length of stay of 2.8 days for the ERAS group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the ERAS protocol applied to BMS, although there is a need of raising awareness, implementation, and standardization of the protocol, with a multimodal, simple, efficient, and cost-effective approach in the care of bariatric patients [30]. Aktimur et al [31] showed significant reduction in the LOS of bariatric surgery patients.…”
Section: Discussionmentioning
confidence: 99%